LEGAL PROTECTION OF ILLEGAL ONLINE LOAN USERS (RESEARCH BY THE YOGYAKARTA REGIONAL FINANCIAL SERVICES AUTHORITY) - Ahmad Tegar Shalahuddin; Ani Yunita (Jurnal Cendekia Hukum, 2022)
Advances in digital technology bring many benefits and changes, including in financial services (Fintech), which use a variety of methods to make it easier for people to transact, such as m-banking, e-commerce, online loans (P2PL), and others. Technological advances are here to make it easier for people to use services, but they can also lead to illegal investments that haven't been regulated by laws and regulations. This could mean that consumers in the financial services sector might not get the best legal protection for these illegal activities. The purpose of this study is to find out how to protect users of illegal P2PL loans in the jurisdiction of Yogyakarta. The method used in this study uses empirical juridical methods. The data sources of this research are primary data in the form of interviews; secondary data from laws and regulations; books; websites; and supported by tertiary data from Indonesian language dictionaries; English dictionaries; and legal dictionaries. The results of the research on the legal protection of illegal P2PL users conducted by OJK DIY together with SWI aim to provide preventive, repressive, and curative legal protection. First, preventive legal protection includes preventive measures, channel effectiveness, education, and performance evaluation. Second, they can be punitive, like giving out punishments based on the law. Third, they can be healing, like taking countermeasures, giving out permits, and giving advice.